RNA editing generates cellular subsets with diverse sequence within populations - Dewi Harjanto (Nature Portfolio, 2016)
RNA editing rate detected from bulk RNA-seq data can vary widely. Here, by constructing a hierarchical Bayesian model, the authors report substantial variance in editing signatures detected by RNA-seq data from both single cells and a cognate bulk sample.